2018
DOI: 10.3390/ijms19103080
|View full text |Cite
|
Sign up to set email alerts
|

Controversial Impact of Sirtuins in Chronic Non-Transmissible Diseases and Rehabilitation Medicine

Abstract: A large body of evidence reports about the positive effects of physical activity in pathophysiological conditions associated with aging. Physical exercise, alone or in combination with other medical therapies, unquestionably causes reduction of symptoms in chronic non-transmissible diseases often leading to significant amelioration or complete healing. The molecular basis of this exciting outcome—however, remain largely obscure. Epigenetics, exploring at the interface between environmental signals and the remo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 140 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…Sirtuins (Sirts) are found in all organisms and are involved in many other processes that occur within cells, including participation in the regulation of the cell cycle and energy metabolism, apoptosis, and oxidative stress processes ( 28 ). In fact, the functions of Sirts have been implicated in the pathogenesis of respiratory diseases, including COPD ( 29 ). Wang et al confirmed the involvement of SIRT5 in the process of COPD by inhibiting CSE-induced apoptosis of lung epithelial cells ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sirtuins (Sirts) are found in all organisms and are involved in many other processes that occur within cells, including participation in the regulation of the cell cycle and energy metabolism, apoptosis, and oxidative stress processes ( 28 ). In fact, the functions of Sirts have been implicated in the pathogenesis of respiratory diseases, including COPD ( 29 ). Wang et al confirmed the involvement of SIRT5 in the process of COPD by inhibiting CSE-induced apoptosis of lung epithelial cells ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 94 SIRTs have been frequently associated with an equivocal role in the pathologic process of aging-associated pathophysiological conditions, including cancer and cardiovascular, muscular, neurodegenerative, bone, and respiratory diseases. 95 , 96 , 97 , 98 Specifically, numerous studies have demonstrated that SIRT-dependent pathways are activated by exercise, which modulates chromatin structure, gene expression and mitochondrial function that lead to beneficial outcomes. 99 In addition to DNA methylation, histone trimethylation in histone-3 lysine-4 after exercise modulates PGC-1α, which upregulates PGC-1α and remodels metabolism of skeletal muscle.…”
Section: Epigenetic Landscape Of Exercise-induced Cardiac Protectionmentioning
confidence: 99%